Identifying Viral Protein Interactions’ Order During Replication and Transcription Processes - Tatiana V. Koshlan; Kirill G. Kulikov (Biophysica)
This study focuses on biochemical pathways of complex biochemical formation, taking into account various thermodynamic parameters that change as the complexity and molecular weight of complex molecules increase. We conducted a study of the co-direction of changes in thermodynamic quantities such as <semantics>lg[Kd]</semantics>, <semantics>TΔS</semantics>, <semantics>Δ(ΔW)</semantics>, and <semantics>lg(cond(W))</semantics> during the transition from a monomer to a dimer and then to a trimer and tetramer. In this work, we assume that the co-direction of changes in thermodynamic quantities as the final molecular formation being achieved signals a higher affinity of molecules among themselves than there is for a biochemical formation, which is characterized by the lack of coordination of the biochemical pathway directions of the final molecular compound. As the studied molecular complexes, we took [LGP2-8dsRNA-LGP2], [VP35]2-dsRNA-[VP35]2, and MARV NPcore proteins with peptides and the complex of MJ20 with antigens from the Bundibugyo strain of Ebola virus. Calculations of biochemical reaction paths were conducted.